Expression of neural crest markers by human embryonic stem cells: an introductory project - Bonic Anita; Poon Mack; Woods Michael G.; Trounson Alan O. (Sciendo, 2016)
Neural crest cells make up a transient migratory population of cells found in all vertebrate embryos. Great advances have been made over the past 20 years in clarifying the molecular basis of neural crest induction and, although much still remains unclear, it appears that it is a process involving several factors acting at different stages of embryogenesis. In the future, an understanding of the precise mechanisms involved in orofacial development, even at the earliest stages, may well be of use to all clinicians interested in the management of these tissues.